Serverless ops a beginner's guide to AWS Lambda and beyond - Hausenblas, Michael (O'Reilly Media, 2017)
The serverless paradigm is going mainstream. Major players such as Amazon, Microsoft, Google, and IBM are among the dozen organizations that now provide serverless compute options in the cloud--also known as Function-as-a-Service. What exactly does the serverless option entail, and how can you gain maximum value from it? This report takes devops practitioners and software architects through several aspects of this new model and shows you how to get started. Author Michael Hausenblas explores several use cases where serverless is a great fit--primarily short-running, stateless jobs in event-driven architectures found in mobile or IoT applications. He also provides a guide for migrating from a monolithic application structure to serverless computing. Compare serverless computing to related paradigms and technologies such as Platform-as-a-Service and remote procedure calls Evaluate the serverless ecosystem, from AWS Lambda and Azure Functions to Iron.io and the Gestalt Framework Look at the serverless paradigm from an operational perspective, and learn why you need a strong devops culture Get a serverless operations field guide, including a walkthrough example of this paradigm Learn how to roll your own serverless infrastructure, rather than rely on the public cloud.
Includes bibliographical references. - Description based on online resource; title from title page (Safari, viewed June 12, 2018)
Keywords: Amazon Web Services (Firm); Cloud computing; Web services; Information technology -- Management; Infonuagique; Services Web; Technologie de l'information; Gestion; Information technology; Management